Implementação de estratégia de atendimento em uma unidade de pronto atendimento de Belo Horizonte baseada nos princípios do Lean Thinking e do Fast Track. - Danilo Borges Matias (2021)
MATIAS, D. B. Implementation of a servisse strategy in na Emergency Care Unit in Belo Horizonte based on the principles of Lean Thinking and Fast Track. 2021. 167 f. Dissertation (Professional Master in Health Services Management) - School of Nursing, Federal University of Minas Gerais. Belo Horizonte, 2021. The Emergency Care Units (ECU) represent an important point of pre-hospital care and access to the system, acting as intermediate units between primary care and hospital emergencies. They often experience episodes of overcrowding, leaving both users and the health care team dissatisfied and eroding the image of health services. The challenges to overcome this situation are many and some management tools have been used to improve this situation. “Lean Thinking” is a set of concepts, methods and tools derived from the Toyota Production System (TPS) and Fast Track is a tool that reflects “Lean Thinking” and consists of a more streamlined service flow for patients considered to be low risk. The objective of this research is to analyze the process of implementing a new service strategy, based on the management tools of Lean and Fast Track in an Emergency Unit in the municipality of Belo Horizonte (MG). The research also assesses the repercussions on the organization of work and the production of care resulting from this intervention. It is a study with a qualitative approach and descriptive purpose of the case study type, complemented by the quantitative approach. The analysis of qualitative data was done through content analysis and the technique used for data collection was the Focus Group. The quantitative analysis, of retrospective and descriptive character, involved a survey of the production data and attendance profile available in the database extracted from the electronic medical record system used in the studied ECU. Information related to the years 2016, 2017, 2018 and 2019 was collected. Based on this information, indicators were constructed that allowed to quantify and characterize the profile of care at the ECU before (2016 and 2017) and after (2018 and 2019) the implementation of the new service strategy. The results obtained show an important improvement in the organization of the flow of patients in the ECU with a reduction in the waiting time for the delivery of care.